Rehabilitation of diseases and lesions of the musculoskeletal system - Ivchenko, A. O.; Kanygina, S. M.; Cherepok, O. O.; Івченко, Анна Олексіївна; Канигіна, Світлана Миколаївна; Черепок, Олександр Олексійович (Запорізький державний медичний університет, 2023)
Study manual is based on the current curriculum and program in the discipline "Physical Rehabilitation and Sports Medicine" for students studying on 222 «Medicine» and 228 «Pediatrics» is compiled in accordance with the curriculum for the training of specialists in the second (master's) level of higher education in the field of study 22 «Health protection» prepared on the basis of the draft higher education standard of the second (master's) level of education for higher education graduates of the Master's degree in the field of study 22 «Health protection».
Keywords: rehabilitation; musculoskeletal system; sports medicine; спортивна медицина; реабілітація; кістково-м'язова система